Reclaiming the feminine in cities at war: female agency, spatial subversion, and linguistic resistance in women-authored literature - Anna Seidel (Studia Rossica Posnaniensia)
This article examines the staging and coding of femininity in literary works focused on cities during wartime, authored by women. Drawing on Judith Butler’s reading of Luce Irigaray and Henri Lefebvre’s The production of space, the analysis centers on the works of Lidiya Ginzburg (Zapiski blokadnogo čeloveka, 1984), Anna Świrszczyńska (Budowałam barykadę, 1974), Zlata Filipović (Le journal de Zlata, 1993), and Yevgenia Belorusets (Anfang des Krieges, 2022). The article argues that these texts challenge abstracting, phallogocentric systems of meaning on two distinct planes. First, they subvert abstract spatial structures forced on urban space by masculine power dynamics, accomplishing this through a perspective that emphasizes the city ‘from below’ and underscores the private, as opposed to the institutional, dimension of urban life. Second, they contest the erasure of the feminine in linguistic structures, shedding light on the oppression experienced by women during war and showcasing narrative and linguistic practices that reclaim agency. The article contends that these four texts not only represent deviations from conventional war narratives but also stage their own female authorship as an appeal against phallogocentric linguistic, spatial, and narrative structures. Consequently, they provide a means to articulate the precarity and marginalization of the feminine within both cities during war and economies of significance wherein the female is subjected to obliteration.